Necessity or Nuisance? Recourse to Human Rights in Substantive International Criminal Law - Gebhard, Julia (2018)
What are chances and challenges of referring to human rights law in defining crimes under international law? Under what circumstances is a reference to human rights law dogmatically appropriate and practically likely? The answers to these questions are explored through a look at the theoretical framework, practical application in jurisprudence as well as empirically through interviews with judges. By highlighting the common roots and the differences between both areas of law, the existing inconsistencies in the application of the law, as well as approaches which could contribute to their solution, the book presents a crucial contribution to the debate on legal certainty and innovation in international criminal law.